Financial sustainability for private higher education institutions - Zanna Cernostana (Institute of Economic Research (IER), 2017)
The development of higher education (HE) is amongst topical issues. The modern society recognises that the most valuable capital is a human being with his/her intellectual potential and this has become the main resource for social and economic development. The important component of the HE systems of many countries is formed by Private Higher Education Institutions (PHEIs), although in each case they have national peculiarities. Today PHEIs undergo difficulties inherent to the entire system of education. The problem of financial sustainability and efficiency of HEIs is becoming urgent. In this context, the most important issue is to deal with developing approaches for quantifying financial sustainability and identifying the indicators of its evaluation. To analyse the financial sustainability of the private sector of HE in Latvia and justify the necessity of an integrated indicator system for financial sustainability evaluation. Include methods of economic and statistic analyses, methods of the analysis and synthesis of economic information, methods of grouping, comparisons, classification, summarising, description and prediction. One of the major issues is the existing gap between the assessment of financial activities of a higher education institution (HEI) and its education activities, which is asserted by accreditation standards; according to these standards, financial and education activities are autonomous entities, hardly interconnected.
Keywords: I22; M21; 330; private higher education; financial sustainability; financial ratio system